Inequalities and Growth in the Southern African Customs Union (SACU) Region - Basdevant, Olivier (IMF Working Papers; Working Paper ;, 2012)
This paper applies the work of Berg and Ostry (2011) to the SACU region, to identify how inequalities have played a role in growth in each of these countries, and elaborates policy options to mitigate the effects of inequalities and foster growth. Lower income inequalities could lead to significant gains, as SACU countries could almost double the duration of their growth periods, with much lower inequalities. While reducing inequalities may be desirable, the design of policies to achieve such objective is not trivial. Policies targeting income inequalities at the sources are expected to be the most effective to reduce inequalities and promote growth. However, direct redistribution, if carefully crafted can also be very effective in reducing inequalities while limiting its potentially negative impact on growth.